Development of an Android-based Computer Based Test (CBT) In Middle School - H., Nurhikmah; Gani, Hamsu Abdul; Pratama, Muh. Putra; Wijaya, Hengki (Journal of Education Technology, 2021)
Teachers still use a semi-conventional evaluation process. Namely, the exam process is carried out by utilizing social media to send students' exam results manually on paper. This kind of evaluation process is less effective and efficient, both in terms of time, the method used and examining exam results which takes a long time and is inaccurate. This study aims to develop a Computer Based Test based on Android. This research method is Research and Development, which is focused on developing a Computer Based Test based on smartphones, especially Android. The development model used refers to the Alessi and Trollip development model. The research subjects were 30 students and 1 mathematics teacher. The instrument used to collect data is a questionnaire. Data collection techniques used are observation, interviews, questionnaires or questionnaires, tests, and documentation. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of the study were the results of validation by material experts obtained an average score of 3.7 (very valid). By media, experts obtained an average score of 3.8 (very valid) so that the Computer Based Test could be tested in the field to determine the practicality where the practicality level met criteria with efficient results. This means that it can be stated that the Android-based Computer Based Test is efficient in the evaluation/exam process on mathematics subjects. Based on the feasibility test of the Computer Based Test, it can be concluded that the use of the Computer Based Test is feasible to be used as a medium for evaluating learning in mathematics subjects.